Legal Counsel Assistance in Court Proceedings in Criminal Cases - Singh, Rakhbir; Supardi; Prasetyo, Handoyo (PT. Multidisciplinary Press Indonesia, 2025)
The Indonesian Criminal Procedure Code (KUHAP) does not differentiate between ethnic groups or nationalities, ensuring that all individuals are treated equally before the court, whether in the District Court, High Court, or Supreme Court. Suspects or defendants are no longer viewed as